IMPLEMENTASI LAYANAN INFORMASI SERTA LAYANAN PENEMPATAN DAN PENYALURAN DALAM PEMBINAAN MINAT DAN BAKAT SISWA DI SMA MUHAMMADIYAH 18 SUNGGAL DELI SERDANG - Mutiara, Mutiara; Lubis, Saiful Akhyar; Daulay, Nurussakinah (UIN Sumatera Utara Medan, 2023)
The purpose of this study was to determine the implementation of information services as well as placement and distribution services in fostering student interests and talents at SMA Muhammadiyah 18 Sunggal. fostering student interests and talents at SMA Muhammadiyah 18 Sunggal? Second, how is the implementation of placement and distribution services in fostering student interests and talents at SMA Muhammadiyah 18 Sunggal school? Third, what are the supporting and inhibiting factors in the implementation of Placement and Distribution services in fostering student interests and talents at the Muhammadiyah 18 Sunggal High School. in a classical way and continuous assistance is carried out, in various problems experienced by students such as in the placement of interests and talents according to their fields. Based on the results of interviews with school principals, deputy principals and BK teachers who have performed these services, it was found that information services as well as placement and distribution services can improve the development of student interests and talents at SMA Muhammadiyah 18 Sunggal.